Single‐Walled Carbon Nanotubes Shock‐Compressed to 0.5 Mbar. Issue 11 (6th November 2017) - Botella, Pablo; Devaux, Xavier; Dossot, Manuel; Garashchenko, Viktor; Beltzung, Jean Charles; Soldatov, Alexander V.; Ananev, Sergey
Abstract : Following our dynamic (shock wave) compression experiments on single‐walled (SW) HiPCO carbon nanotubes (CNTs) [M. Noël et al., Phys. Stat us Sol idi RRL 2014, 8, 935], we extended the range of shock compression to ≈0.5 Mbar in quest of new forms of nanostructured carbon derived from crushed SWCNTs. The material recovered after shock is characterised by multi‐wavelength Raman spectroscopy and high‐resolution transmission electron microscopy (HRTEM). Two distinct types of material are identified: (i) multi‐layer graphene (MLG) and (ii) a mixture of disordered nanometer‐sized graphene clusters and amorphous carbon. No diamond‐like carbon or carbon nano‐onions are found in the sample. The coherent scattering size of MLG clusters ( L a ) is estimated at 30 nm from the D‐ to G‐band intensity ratio dependence on the photon excitation energy. We demonstrate the capabilities of Raman spectroscopy for characterisation and analysis of the multi‐phase spectra of disordered carbon. Particulars of CNT transformation to other structural forms of carbon at high pressure/temperature are discussed. Abstract : By high‐resolution transmission electron microscopy (HRTEM) and Raman spectroscopy, the authors identify two types of material in the sample recovered after shock compression of HiPCO single‐walled carbon nanotubes (SWCNTs) to 0.5 Mbar: multi‐layer graphene (1) and a two‐phase material (2) composed of nano‐clustered graphene and amorphous carbon.